Preliminary insights : isomorphism and effectiveness of performance auditing issues follow-up - Umor, Sarimah; Zakaria, Zarina; Sulaiman, Nor Adwa; Kutty, Rasheed Mohamed (International Journal of Engineering and Technology, 2018)
Reality of current times of scarce public budgets drive the public administrations to achieve their goals in the most economical, efficient and effective manner as depicted in the key concepts of performance auditing. Performance auditing as one of the activity that the Supreme Audit Institution (SAI) uses to assure economy, efficient and effective use of public funds. Equally importance is the follow-up in which according to ISSAI 3000 is a part of every performance auditing activity. Follow-up is necessary for ensuring that audit recommendations are well addressed by identifying the sources of inefficiency. Consequently, appropriate action can be taken to improve public organization performance.Â  Follow-up on performance auditing issues appear to be important to re-check on the responsiveness towards audit recommendation on various issues raised pertaining to improper use of public fund. In particular, the focus of this paper on follow-up brings about different type of institutional pressure which have not been well explored. Since audit recommendations are not fully implemented, repetitive issues are being disclosed to the public which at the end create public service performance dissatisfaction. Lack of follow-up may cause a problem to measure the real value and impact of performance audit. This paper highlights different types of pressure which can be explained by three forces of isomorphism namely coercive, mimetic and normative as a theoretical lens to explain its effect towards follow-up effectiveness.